IoT-Based ECG Monitoring System for Health Care Applications - Sohit Agarwal, Devashish Dasaya (Mathematical Statistician and Engineering Applications, 2022)
To better comprehend our environment, the new IoT architecture allows for the creation of tiny devices with sensing, processing, and communication capabilities. These devices may then be used to create sensors, embedded systems, and other "services." Using the power of the Internet of Things, we describe an electrocardiogram (ECG) system for the continuous monitoring of cardiovascular health through secured data transmission (IoT). Tiny sensors, embedded devices, and other "things" with sensing, processing, and communication capabilities are now feasible thanks to the current paradigm of the Internet of Things. The Internet of Things (IoT) and other connected medical technologies have allowed for remote monitoring of patients' vital signs in real time. In the event of a corona-virus pandemic, there would be a dramatic increase in the number of persons seeking medical assistance, making regular patient monitoring essential. Concerns concerning the privacy of IoT data remain significant, as evidenced by the transfer of patients' huge amounts of personal health information made by those who do not intend to share their own medical information. Because of recent developments in IoT technology, "smart objects" (things) can now have real-time Internet communication. Sensors, a consolidated processing unit, and a database platform are all useful tools for IoT healthcare applications. This paper includes an Internet of Things (IoT)-enhanced electrocardiogram (ECG) monitoring system that can either send data to a server in real time or create an ECG graph that can be seen on a Smartphone with an accompanying app. The patient's current temperature, humidity, and heart rate are all shown in the app. As part of this effort, we present a lightweight method for rapidly updating data at a distance.